2023
DOI: 10.1002/smll.202302698
|View full text |Cite
|
Sign up to set email alerts
|

Identifying And Unveiling the Role of Multivalent Metal States for Bidirectional UOR and HER Over Ni, Mo‐Trithiocyanuric Based Coordination Polymer

Abstract: Urea oxidation reaction (UOR), an ideal alternative to oxygen evolution reaction (OER), has received increasing attention for realizing energy‐saving H2 production and relieving pollutant degradation. Normally, most studied Ni‐based UOR catalysts pre‐oxidate to NiOOH and then act as active sites. However, the unpredictable transformation of the catalyst's structure and its dissolution and leaching, may complicate the accuracy of mechanism studies and limit its further applications. Herein, a novel self‐support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Deprotonated CON 2 further undergoes intramolecular N–N coupling, resulting in N 2 production and release. 48,49 In addition, the different perspectives of the Ba–Ni(OH) 2 structure are shown in Fig. 5(b–d).…”
Section: Resultsmentioning
confidence: 99%
“…Deprotonated CON 2 further undergoes intramolecular N–N coupling, resulting in N 2 production and release. 48,49 In addition, the different perspectives of the Ba–Ni(OH) 2 structure are shown in Fig. 5(b–d).…”
Section: Resultsmentioning
confidence: 99%
“…The different coordination types ( e.g. , Fe–S 2 N 2 , 134 Fe–S 4 , 134 Mo–S 2 N 2 , 133 Co/Ni–Se 4 , 135 and Co–O 2 N 2 136 ) have also been reported to regulate their intrinsic HER activity. One source of electrical conductivity in MOFs stems from their π-conjugated frameworks, enabled through the M–N x coordination between metal nodes and conjugated organic ligands.…”
Section: Organic Polymers As Emerging Electrocatalystsmentioning
confidence: 99%
“…Liu et al reported the multi-interface coil-like NiS-Ni 2 P/Ni electrocatalyst prepared on NF. The NiS/Ni and Ni 2 P/Ni interfaces were served as electrochemical active sites and exhibited superior HER catalytic activity with overpotentials of 115 and 53 mV at 10 mA cm -2 in neutral and alkaline electrolyte [88] .…”
Section: Interface At Heterostructuresmentioning
confidence: 99%